PENGARUH REKRUTMEN APARATUR SIPIL NEGARA TERHADAP PENYELENGGARAAN PELAYANAN PUBLIK (Studi di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Halmahera Utara) - HARIAWAN, SHINTIA; KIYAI, BURHANUDDIN; KOLONDAM, HELLY (Sam Ratulangi University, 2019)
This study aims to determine and analyze the Effect of Recruitment on the Implementation of PublicServices in the Population and Civil Registration Office of North Halmahera Regency. The research methodthat I use in this research is quantitative research methods. Data and information were collected through aquestionnaire technique and completed with interview data source techniques/research respondents wereall employees in the Department of Population and Civil Registration of North Halmahera Regency as manyas 36 people.The analysis techniques used by testing hypotheses are frequency tables, product-momentcorrelations and simple linear regression. Based on the description of the data it turns out that most of therespondents who gave an assessment of the recruitment variable of the State Civil Apparatus were in thecategory of â€œhighâ€ or at 66,66%, then as many as 12 employee respondents or at 33,33% who state that therecruitment of the State Civil Apparatus in the Office Population and Civil Registration of NortHamlmahera Regency is in the â€œmediumâ€ category, while the category of â€œlawâ€ is not out of 36 employeerespondents who were interviewed in the North Halmahera Regency Population and Civil RegistrationService. While public service variable in the North Halmahera Regency Population and Service are in theâ€œhighâ€ category or 52,77%, then 17 employee respondents or 47,22% stated that public services in theHalmahera Regency Population and Civil Registration Service in the â€œmediumâ€ category, while in theâ€œlowâ€ category there isnâ€™t.Keywords: Recruitment of State Civil Apparatus, Public Services